Sentence and Discourse 2015
DOI: 10.1093/acprof:oso/9780198739418.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Thepassé composéin Old French and Modern French: evolution or revolution?

Abstract: This chapter is concerned with determining how strictly ordered sequences of events described by the passé composé (PC) in Old French should be accounted for. The analysis here proposed will combine (i) insights from analyses claiming that this tense did not have (yet) a past perfective semantic content (e.g. Martin 1971), but really behaves like a resultative narrative (‘perfective’) present in many of the above configurations, with (ii) insights from analyses claiming that it had perfective uses in some spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…Furthermore, as an unambiguous diagnostic, the presence of a vP-edge demarcating element such as an infinitive or pastparticiple is required. In the latter case, recall that the compound past tense was nowhere near as ubiquitous in the medieval period as it is in the contemporary language (Harris 1978;Rickard 2003: 56;Caudal 2015). In sum, we should therefore not be surprised that the unambiguous cases are not extremely frequent in text, as we require the coalescence of two syntactic factors: an overt postverbal subject and the presence of a diagnostic element for the position of that subject.…”
Section: G-inversion and R-inversionmentioning
confidence: 95%
“…Furthermore, as an unambiguous diagnostic, the presence of a vP-edge demarcating element such as an infinitive or pastparticiple is required. In the latter case, recall that the compound past tense was nowhere near as ubiquitous in the medieval period as it is in the contemporary language (Harris 1978;Rickard 2003: 56;Caudal 2015). In sum, we should therefore not be surprised that the unambiguous cases are not extremely frequent in text, as we require the coalescence of two syntactic factors: an overt postverbal subject and the presence of a diagnostic element for the position of that subject.…”
Section: G-inversion and R-inversionmentioning
confidence: 95%
“…
This paper investigates the diachronic evolution of so-called aspectual coercion (de Swart 1998, Bary & Egg 2012 in French, with respect to two major tenses, namely the simple past (passé simple) (PS) and compound past (passé composé) (PC); it will more specifically bear on cases of inchoative readings. Throughout a study spanning several diachronic stages and capitalizing on earlier work (Caudal 2015a, Caudal 2015b, Caudal, Burnertt & Troberg 2016, it will be shown that the PC and the PS exhibit striking differences in their acquisition of inchoative coercions, with the PC consistently lagging behind the PS in some respects. Initially, at the Old French period, the PC was totally deprived of any coercive power w.r.t.
…”
mentioning
confidence: 87%
“…discourse connectives, specific types of discourse relations); some amount of contrast with the inchoative potential of the PS in Modern French is certainly predicted to exist. Similarly, Caudal (2015a) demonstrates that the PC did not have bona fide perfective uses prior to the 15 th c.; so its inchoative potential with stative utterances should vary through time.…”
mentioning
confidence: 99%
“…De différentes façons, les travaux précédemment cités se focalisent sur le fait manifeste suivant dont ils tâchent de rendre compte : les formes analytiques en français contemporainet tout particulièrement le passé composésont susceptibles d'avoir deux valeurs principales, nommées suivant les auteurs : (i) accomplie (Gosselin, 1996), ou résultative (Buridant, 2000 ;Caudal et Vetters, 2007 ;Caudal, 2015 ;Apothéloz, 2016), comme en (13) ; et (ii) aoriste de discours (Benveniste, [1959] 1966), aoristique (Gosselin, 1996(Gosselin, , 2017, perfective (Caudal et Vetters, 2007), antérieure (Buchard et Carlier, 2008), ou processive (Apothéloz, 2016), comme en 14 En (13), le PC représente le procès sortir dans sa phase post-processuelle au présent ; en (14), il représente ce même procès dans sa phase processuelle au passé, concurrençant par-là la forme synthétique du passé simple.…”
Section: Dualité Des Sens Produits Par Le Passé Composé En Discours Eunclassified
“…Cette troisième étape s'étale de l'ancien français au français moderne (cf. notamment Caudal et Vetters, 2007 ;Caudal, 2015 ;Apothéloz, 2016), avec une charnière entre français classique (XVII e siècle) et français moderne (XVIII e siècle) (Caron et Liu, 1999) : le PC, qui jusqu'alors n'admettait de circonstants qu'incluant t 0 , commence, à la fin du XVII e siècle, à pouvoir être flanqué de tout type de circonstant passé, construction qui se développe au XVIII e siècle. En récit rétrospectif, il concurrence le passé simple 15 en tant que temps narratif : 23 Actuellement le PC en français a cantonné le PS dans quelques niches discursives étroites.…”
Section: Dualité Des Sens Produits Par Le Passé Composé En Discours Eunclassified